Det kgl. Landhusholdningsselskabs Generalforsamling den 17de December 1879. - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Det kgl. Landhusholdningsselskabs Generalforsamling den 17de December 1879.